The different Between Male and Female in Using Indirect Speech Act in Having Relationship When Texting in WhatsApp - Lubis, Siti Isma Sari; Harmawan, Violintikha; Rambe, Armita Novriana; Hutasuhut, Nurul Inayah (English Education : English Journal for Teaching and Learning, 2024)
Men and women typically communicate closely with one another. As a result, dating relationship notions are common in society, particularly among young adults. Both men and women will always have communication goals while they are in a relationship. They communicate with each other via social media in addition to in-person interactions. WhatsApp is one of the most used social media platforms in today's world. The purpose of this study was to determine whether men or women frequently utilize indirect speech when texting their partners on WhatsApp. Three couples that communicate via WhatsApp are the subjects of this study. They are between the ages of 20 and 25. Within two weeks, the data was gathered by recording their message history. According to Clark (1977), the data was analyzed by classifying it into direct and indirect speech acts. It was discovered that women are more likely than men to use indirect speech acts. Ten indirect speech acts were performed by the females of three couples, whereas only three were delivered by the man, according to three conversation histories.